2016
DOI: 10.1021/acs.jpca.6b09666
|View full text |Cite
|
Sign up to set email alerts
|

Toward Molecular Magnets of Organic Origin via Anion−π Interaction Involving m-Aminyl Diradical: A Theoretical Study

Abstract: Here we study a set of novel magnetic organic molecular species with different halide ions (fluoride, chloride, bromide) absorbed ∼2 Å above or below the center of an aromatic π-ring in an m-aminyl diradical. Focus is on the nature of anion-π interaction and its impact on magnetic properties, specifically on magnetic anisotropy and on intramolecular magnetic exchange coupling. In the development of single molecule magnets, magnetic anisotropy is considered to be the most influential factor. A new insight regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 143 publications
2
16
1
Order By: Relevance
“…The spin–spin interaction between the unpaired electrons in the diradicals is associated with the average distance between unpaired spins . The decrease of the centroid distance between SOMOα and SOMOβ results in the strengthening spin–spin interaction in the BS state, which is an influential factor in magnetic anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…The spin–spin interaction between the unpaired electrons in the diradicals is associated with the average distance between unpaired spins . The decrease of the centroid distance between SOMOα and SOMOβ results in the strengthening spin–spin interaction in the BS state, which is an influential factor in magnetic anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…Although increasing the size of the doped nanoclusters slightly lowers the diradical character, all the NV nanoclusters have large diradical characters and can be viewed as standard diradicals with the expected AFM or FM spin couplings (Table and Table S2). , The above observations inspire us to use the doping modification to assign the NV nanoclusters expected magnetic coupling characteristics and magnitudes, together with controlling the size of the nanoclusters, for designing the targeted endohedral σ-diradical NV diamond nanocluster magnets.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, an application of these three pairs of tautomers in the field of magnetic information storing or switch controlling might be acceptable. Moreover, recent studies , have shown a possible method to produce high-spin coupling molecular magnets with triplet ground state by introducing halide ions, which may expand the applications of our designs to low-to-high spin transformation (see the Supporting Information for details). Of course, apart from all of the discussions above, the specific way to make full use of them needs more in-depth studies.…”
Section: Resultsmentioning
confidence: 99%